ELABORATION OF CLINICAL PRACTICE GUIDELINES: INTEGRATION BETWEEN UNIVERSITY AND HOSPITAL UNIT - Derdried Athanasio Johann; Priscila Mingorance; Luciana Souza Marques De Lazzari; Edivane Pedrolo; Tatiana Queiroz Ribeiro de Almeida; Mitzy Tannia Reichembach Danski (Universidade Federal do Paraná, 2012)
The setbacks confronted in daily nursing routines are themes in undergraduate and postgraduate research, while the healthcare professional at the bedside needs to update her skills and seek the best evidence so as to offer quality care. The authors reflect on how academia can integrate itself to practice and thus contribute to improving care by elaborating and implanting clinical practice guidelines. The busy healthcare professionals sometimes do not have the opportunity to consider their literature search tools and select the best evidence to implant in their unit. For academia, however, this type of research is habitual, with the elaboration of clinical practice guidelines and their implantation in the units researched being perfectly viable. An objective was to reflect on the integration of university and hospital units, with a focus on the joint elaboration of clinical practice guidelines.